PELAKSANAAN SUPERVISI DALAM PEMBELAJARAN DI ERA DIGITAL: Introduction, Research Method, Study Theory, Research Results and Discussion, Conclusion - Annisa Nur Fathiyah; Gindara Dwi Hendrawati; Subandi Subandi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to explore the implementation of supervision in learning in the digital era, which is becoming increasingly important along with the development of information technology. The background of this study focuses on the challenges faced by educators in integrating technology into the learning process and the need for effective supervision support. The method used in this study is a literature study, in which the author collects and analyzes data from various relevant literature sources. The findings of the study indicate that data-based and technology-based supervision can improve the quality of learning and assist teachers in adapting more innovative teaching methods. The implications of this study emphasize the importance of training and guidance for teachers to optimally utilize digital technology in the learning process. Thus, this study provides recommendations for educational policy makers to strengthen the supervision system in the context of digital education.